Structural Controls of Uranium Mineralization in the Basement of the Athabasca Basin, Saskatchewan, Canada. (24th February 2021) - Benedicto, Antonio; Abdelrazek, Maher; Ledru, Patrick; MacKay, Cameron; Kinar, Dwayne
Abstract : The occurrence of unconformity-related uranium mineralization requires the combination of three components: fluids with the right composition, geochemical traps with the right agents that produce precipitation, and structural traps with the right geometry. In the Athabasca Basin unconformity-related uranium deposits, while basinal brines are commonly accepted as the principal mineralized fluids and graphite and gases (CH4, CO2, and H2 S) are well known as the reductants, only few case studies describing structural traps are published. A number of recent works, including numerical modelling, have improved the understanding of the role of inherited shear zones on fluid flow and the development of uranium deposits at a micro- and regional-scale. Nevertheless, there is still a lack of knowledge about the meso- or deposit-scale structural controls that lead to the present (and potentially predictive) localization of uranium deposits along a given shear zone. The present work examines new structural data from drill holes and deals with (i) the identification of mesoscale structural traps that lead to the formation of the Athabasca unconformity-related uranium deposits hosted within the basement and (ii) with the understanding of the role and mode of reactivation of the inherited shear zones. The Sue deposits (McClean Project), the Tri-Island showing (Martin Lake Project) in the Eastern Athabasca, and the Spitfire prospect (Hook Lake Project) in the Western Athabasca have been selected for a detailed analysis of structures and related uranium mineralization. The structural analysis performed brings new insights about the mesoscale structural controls, the role the inherited ductile fabric had on the mode of brittle reactivation and to trap mineralization, and the tectonic regime to which basement-hosted uranium deposits may be associated in the Athabasca Basin.